The mental health and legal perspective of child sexual abuse: a case series - Swain, Sarada P.; Behura, Sushree S.; Swayamsidha (International Journal Of Community Medicine And Public Health, 2025)
Child sexual abuse (CSA) is not only a health concern, but also remains a socially neglected issue in every country. It has significant psychological and social issues that are often underreported. The immediate psychological effects have a negative impact on the child’s mental health and social development, creating long-term physical and mental health consequences. CSA victims are always at risk of anxiety, adjustment issues, dissociation, depression, dysfunctional sexual behaviors, somatization, and suicidality. The long-term mental health morbidities and sociocultural issues are frequently experienced by the adult survivors of CSA.